Economic Consequences of Political Persecution (updated research) - Radim Boháček; Michal Myck (Institute of Labor Economics (IZA), 2025)
We examine the consequences of political persecution under the communist regime on labor market outcomes using life history data from the Czech sample of the Survey of Health, Ageing and Retirement in Europe. The risk of persecution is instrumented using unique administrative data on the intensity of political oppression. We find strong evidence of career degradation as a consequence of persecution-driven job losses. Our estimates suggest that earnings in jobs following such a loss carried a penalty of over 60 percent that accumulated over time to substantially lower retirement benefits. We document the gravity of economic consequences for ordinary citizens persecuted by the authoritarian regime as well as effective compensating schemes implemented by democratic governments after 1989.
Older version: https://hdl.handle.net/10419/174046
Keywords: J70; J31; N34; C21; 330; political persecution; discrimination; wage differentials; communist regimes; life histories